Inhibition of farnesyl pyrophosphate synthase alleviates cardiomyopathy in diabetic rat. Issue 6 (19th March 2023) - Liu, Xiaowei; Liu, Yajun; Tang, Lijiang; Du, Changqing
ABSTRACT: This study investigated the effects of ibandronate (IBN) on cardiomyopathy remodeling in diabetic rats. A rat model of diabetic cardiomyopathy (DCM) was established by supplementing them with a high-calorie diet combined with a low dose of streptozotocin (STZ). The diabetic rats received IBN (5 µg/kg per day) or normal saline subcutaneously for 16 weeks. The hematoxylin and eosin (H&E) and Masson's trichrome staining were performed for evaluating the myocardial morphologies of the rats. Echocardiography and cardiac catheter were performed to assess their cardiac functional parameters. The protein levels of connective tissue growth factor (CTGF), farnesyl pyrophosphate synthase (FPPS), and mitogen-activated protein kinase (MAPK) were determined using Western blot analysis. RhoA activation was detected using a small GTP protease-linked immunosorbent assay (GLISA). The diabetic rats showed the development of moderate hyperglycemia, insulin resistance, hyperlipidemia, myocardial fibrosis, FPPS overexpression, cardiac systolic, and diastolic dysfunction. Inhibiting the FPPS could ameliorate myocardial hypertrophy and ﬁbrosis. These anatomical findings were accompanied by a significant improvement in heart function. Furthermore, the inhibition of FPPS, the increased activation of RhoA, and phosphorylation of p38 and extracellular signal-regulated kinase (ERK)1/2 in DCM decreased significantly with the treatment of IBN. This study for the first time demonstrated that the upregulation of FPPS expression might be involved in diabetic myocardial remodeling in diabetes mellitus (DM). In addition, IBN might exert its inhibitory effects on myocardial tissue remodeling by suppressing the RhoA/ERK1/2 and RhoA/p38 MAPK pathways in DCM.